In Vitro Cytotoxic and Anthelmintic Activities of Leonurus sibiricus L. - Saha, M. R.; Ul Bari, F.M.S.N.; Rahman, M. A.; Islam, M. A. (Journal of Scientific Research, 2012)
This study investigated the cytotoxic and anthelmintic activities of Leonurus sibiricus L. (commonly known as Raktodrone in Bangladesh) belonging to the family Labiatae. The dried leaves and roots of L. sibiricus were extracted with methanol and fractionated by modified Kupchan method. The crude methanolic extracts as well as its soluble fractions of petroleum ether, ethyl acetate and chloroform were screened for cytotoxic activity using brine shrimp lethality bioassay. They were found to possess significant cytotoxic activities. The LC50 values of crude extract of leaves and its pet-ether, ethyl acetate and chloroform soluble fractions were 1.0, 2.0, 2.11 and1.33 µg/ml, respectively. On the other hand, the LC50 of crude methanolic extract of roots and fractions of pet-ether, ethyl acetate and chloroform were 2.0µg/ml, 2.81 µg/ml, 3.55 µg/ml and 7.58µg/ml, respectively. Vincristine sulphate was used as positive control. The crude methanol extract of leaves and roots also showed very good anthelmintic activities as determined against the earthworms, Pheretima posthuma. The study confirms the moderate anthelmintic and potent cytotoxic activities of leaf and root extracts of L. sibiricus. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.9998 J. Sci. Res. 4 (3), 721-727 (2012)